Determination of Allowance Time by Work Sampling and Heart Rate in Manufacturing Plant in Juárez México - Karen Y. Ferreira García; Jorge de la Riva Rodriguez; Jaime Sánchez Leal; Rosa M. Reyes-Martínez; Arturo Woocay Prieto (Journal of Engineering)
We propose a methodology for determination of Allowance Time (AT), based on heart rate and work sampling of a production line composed of thirteen stations operated by four workers. The current production line presents a high rate of personnel turnover and absenteeism and with an AT value established by the company of 6.3%. The AT determination is of critical importance, given that through this the workers need to maintain their work rhythm at 100% during the entire workday without fatigue. The resulting allowance after the study was 15% instead of 6.3%, increasing the standard time and causing a decrease in personnel turnover and absenteeism and consequently increasing the production capacity and the reduction of costs.